2013
DOI: 10.1111/tbj.12157
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy for Risk-Reducing Mastectomy

Abstract: Risk-reducing mastectomy (RRM) confers 90-95% decreased risk of breast cancer, and may reduce mortality, especially in high-risk groups such as BRCA carriers. Risk of occult disease in RRM specimen is ~5%. This demands axillary staging: sentinel lymph node (SLN) biopsy is no longer possible, axillary clearance confers significant risks and may prove negative. Contemporaneous SLN biopsy allows axillary staging with minimal further dissection. Women undergoing RRM and SLN biopsy between June 2005 and July 2010 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…The median number of lymph nodes removed from operated breasts was 1 (range 1-2), which is in agreement with the results of other studies (1.35 [ 10 ], 1.46 [ 25 ], and 2 [ 31 ]). This assessment is important because a higher number of biopsied lymph nodes reduce the false negative rate but also increase morbidity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The median number of lymph nodes removed from operated breasts was 1 (range 1-2), which is in agreement with the results of other studies (1.35 [ 10 ], 1.46 [ 25 ], and 2 [ 31 ]). This assessment is important because a higher number of biopsied lymph nodes reduce the false negative rate but also increase morbidity.…”
Section: Discussionsupporting
confidence: 92%
“…Our group reinforces the importance of MRI at a short interval before surgery, since all our patients had a BRCA1/2 pathogenic mutation and, therefore, a higher risk both for occult and for interval carcinoma. In fact, in spite of being a high-risk group, the occult carcinoma incidence in our study (5%) was similar to that reported by others (6.0% [ 3 ], 4.8% [ 10 ], and 1.76% [ 31 ]) and the same can be concluded for our occult invasive carcinoma rate (2.5% versus 2% [ 17 ], 1.2% [ 10 , 31 ], and 0% [ 3 ]).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the risk of lymphedema was high in the group with ALND, they suggested SLNB use during CPM because they did not find any differences in lymphedema between the groups with and without SLNB. Burger et al (20) found only one occult ILC and three lobular in situ neoplasms in 83 PMs. They suggested SLNB because they did not see lymphedema in any patient and thought that adding SLNB did not prolong the duration of operation.…”
Section: Discussionmentioning
confidence: 96%
“…The surgeons using routine SLNB during CPM suggest that SLNB cannot be performed after mastectomy, so in case of occult invasive malignancy at CPM, ALND will be mandatory at the second session, which may cause an increase in morbidity. In addition, many authors suggest that they do not observe lymphedema or the risk is similar in the cases in which SLNB is not performed (1,4,20). They also state that SLNB is helpful to find possible cross-metastases from index tumor (1).…”
Section: Discussionmentioning
confidence: 99%